Differential expression of p73alpha in normal ectocervical epithelium, cervical intraepithelial neoplasia, and invasive squamous cell carcinoma - Nenutil, R; Ceskova, P; Coates, P J; Nylander, K; Vojtesek, B (International journal of gynecological pathology, 2003)
The TP73 gene is a member of the p53 family and through differential promoter usage and alternative splicing can encode a number of different isoforms that have distinct properties. p73 proteins are widely expressed in neural, epithelial, and hemopoietic cells and are proposed to have roles in the development and differentiation of various cell types and in tumorigenesis. The authors have developed a novel monoclonal antibody that is specific for p73alpha to study the expression of this individual isoform in normal and neoplastic cervical epithelium. In normal epithelium, p73alpha is restricted to nonproliferating cells at the base of the epithelium, whereas other p73 isoforms are found in the proliferative zones higher up in the epithelium. In cervical cancers, p73alpha expression is commonly lost, although other p73 isoforms are present at high levels. In particular, the authors found that invasive islands lose p73alpha expression when compared with the overlying intraepithelial lesion. These results show a tight regulation of p73 isoform expression in cervical epithelium and imply that different isoforms of p73 enhance or suppress neoplastic cell growth. These data raise the possibility that reactivation of p73alpha might be beneficial in cervical carcinoma. In addition, the absence of p73alpha in cervical cancer represents a potentially useful tool for the diagnosis of this disease.
Keywords: tumor supresorové geny; Cervix Uteri; DNA-Binding Proteins; epitel; regulace genové exprese u nádorů; Humans; cervix uteri; DNA vazebné proteiny; Biomarkers, Tumor; nádorové supresorové proteiny; Genes, Tumor Suppressor; Antibodies, Monoclonal; Female; Tumor Protein p73; nádory děložního čípku; jaderné proteiny; lidé; Immunohistochemistry; Tumor Suppressor Proteins; imunohistochemie; nádorové biomarkery; protein - isoformy; Protein Isoforms; ženské pohlaví; dysplazie děložního hrdla; Nuclear Proteins; Epithelium; monoklonální protilátky; Uterine Cervical Neoplasms; Uterine Cervical Dysplasia; spinocelulární karcinom; Carcinoma, Squamous Cell; protein p73; Gene Expression Regulation, Neoplastic